Concepts in multimodal discourse analysis with examples from video conferencing - Norris, Sigrid (Yearbook of the Poznan Linguistic Meeting, 2016)
This article presents theoretical concepts and methodological tools from multimodal (inter)action analysis that allow the reader to gain new insight into the study of discourse and interaction. The data for this article comes from a video ethnographic study (with emphasis on the video data) of 17 New Zealand families (inter)acting with family members via skype or facetime across the globe. In all, 84 social actors participated in the study, ranging in age from infant to 84 years old. The analysis part of the project, with data collected between December 2014 and December 2015, is ongoing. The data presented here was collected in December 2014 and has gone through various stages of analysis, ranging from general, intermediate to micro analysis. Using the various methodological tools and emphasising the notion of mediation, the article demonstrates how a New Zealand participant first pays focused attention to his engagement in the research project. He then performs a semantic/pragmatic means, indicating a shift in his focused attention. Here, it is demonstrated that a new focus builds up incrementally: As the participant begins to focus on the skype (inter)action with his sister and nieces, modal density increases and he establishes an emotive closeness. At this point, the technology that mediates the interaction is only a mundane aspect, taken for granted by the participants.